Risk of cancer in the rectal remnant after ileorectal anastomosis in patients with familial adenomatous polyposis: Single center experience. Issue 4 (16th January 2015) - Maehata, Yuji; Esaki, Motohiro; Nakamura, Shotaro; Hirahashi, Minako; Ueki, Takashi; Iida, Mitsuo; Kitazono, Takanari; Matsumoto, Takayuki
Abstract : Background and Aim: We aimed to evaluate the long‐term risk of cancer in the rectal remnant in patients with familial adenomatous polyposis after ileorectal anastomosis. Methods: Cumulative incidence and clinicopathological characteristics of cancer in the rectal remnant were retrospectively investigated in 27 patients with familial adenomatous polyposis who had undergone ileorectal anastomosis. Results: During the follow‐up period ranging from 3.0 to 35.0 years (median, 21.1 years), cancer in the rectal remnant developed in 10 patients. Cumulative risk of cancer in the rectal remnant 30 years after surgery was 57%. Five patients had metastases and three patients died of cancer in the rectal remnant after proctectomy. There was a trend towards a higher incidence of cancer in the rectal remnant in patients with small‐intestinal adenoma and congenital hypertrophy of the retinal pigment epithelium. Multivariate analysis revealed that the ocular lesion was an independent risk factor associated with cancer in the rectal remnant. Conclusion: Subtotal colectomy with ileorectal anastomosis does not seem to be an appropriate prophylactic surgery in patients with familial adenomatous polyposis.